Elemental Metabolomics: Modulation of Egg Metallome with Flavonoids, an Exploratory Study - Athanasios C. Pappas; Evangelos Zoidis; Michael Goliomytis; Panagiotis E. Simitzis; Kyriaki Sotirakoglou; Maria A. Charismiadou; Christos Nikitas; George Danezis; Stelios G. Deligeorgis; Constantinos A. Georgiou (MDPI AG, 2019)
The basic principles of elemental metabolomics were applied to investigate whether alteration of egg metallome could be achieved after two flavonoids addition, namely hesperidin and naringin in diets of laying hens. A total of 72 hens were divided into six groups: Control (C) (basal diet), E1 (750 mg hesperidin/kg diet), E2 (1500 mg hesperidin/kg diet), N1 (750 mg naringin/kg diet), N2 (1500 mg naringin/kg diet), and VE (200 mg vitamin E/kg diet). The same diet was provided to birds of all treatments, with the exception of added supplements. The diets had the same vitamin and mineral premix; thus, all birds received the same number of elements because no differences on feed intake existed. The egg elemental profile consisted of As, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Pb, Sb, Se, Sr, V, Zn, and was determined using ICP-MS. Flavonoid supplementation altered the elemental profile. Most notably, in both albumen and yolk, hesperidin increased Ni, Pb, and Sr concentration while it decreased that of Co and Sb. Naringin increased Cd, Cr, Cu, Ni, and V and lowered the concentration of Co and Sb in both yolk and albumen. Vitamin E supplementation, in comparison to the control, decreased Co in both albumen and yolk and also raised Sb in albumen. Flavonoid presence led to the differences in deposition of certain trace minerals in egg compared to that of hens fed a basal diet or a diet with vitamin E supplementation.